2015
DOI: 10.1097/aln.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational Anesthetics Disrupt Postsynaptic Density Protein-95, Drosophila Disc Large Tumor Suppressor, and Zonula Occludens-1 Domain Protein Interactions Critical to Action of Several Excitatory Receptor Channels Related to Anesthesia

Abstract: Background We have shown previously that inhaled anesthetics disrupt the interaction between the second postsynaptic density protein-95, Drosophila disc large tumor suppressor, and zonula occludens-1 (PDZ) domain of postsynaptic density protein-95 (PSD-95) and the C-terminus of N-methyl-D-aspartate receptor subunits NR2A and NR2B. Our data indicate that PDZ domains may serve as a molecular target for inhaled anesthetics. However, the underlying molecular mechanisms remain to be illustrated. Methods Glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…2022 The isoflurane concentration was reduced by 0.1% for 20 min if the animal did not right itself, and the righting reflex was subsequently retested. RREC 50 was calculated for each mouse as the mean value of the anesthetic concentrations that just permitted and just prevented the righting reflex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2022 The isoflurane concentration was reduced by 0.1% for 20 min if the animal did not right itself, and the righting reflex was subsequently retested. RREC 50 was calculated for each mouse as the mean value of the anesthetic concentrations that just permitted and just prevented the righting reflex.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Shank3 protein is a molecular scaffolding protein essential for synapse formation and for mediating N-methyl-D-aspartate receptor (NMDAR)- and metabotropic glutamate receptor (mGluR)-induced excitatory synaptic transmission, 1114 potential sites of anesthetic action. 1520 We have shown previously that inhalational anesthetic agents can disrupt the interaction of other scaffolding proteins (PSD93 and PSD95) with NMDA and AMPA receptors, resulting in a reduction of the minimum alveolar concentration (MAC) required for anesthesia 21,22 . Shank binds to PSD95-associated protein GKAP and assembles into a complex of Shank/GKAP/PSD95, coupling NMDAR-PSD95 complexes to regulators of the actin cytoskeleton 23 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings revealed the PDZ domain as a new molecular target for inhalational anesthetics. Using a surface plasmon resonance-based BIAcore assay, binding of PSD-95 PDZ2 to NR2B C-terminus was shown to be disrupted by isoflurane in real time 86 . These results demonstrated that anesthetics can disrupt the PDZ domain-mediated protein interactions between PSD-95 and the NMDA receptor and suggest downstream effects on synaptic plasticity.…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…These results demonstrated that anesthetics can disrupt the PDZ domain-mediated protein interactions between PSD-95 and the NMDA receptor and suggest downstream effects on synaptic plasticity. Given the critical role of PSD-95 and NMDA receptors in synapse development, it has been proposed that anesthetics such as isoflurane and sevoflurane might interfere with brain development by disrupting the interactions between these proteins 86 .…”
Section: Nmda Receptorsmentioning
confidence: 99%
“…Various in vitro studies have found that the enhancement of inhibitory neurotransmitter function and inhibition of excitatory neurotransmitter function to be plausible mechanisms underlying the action of inhalation anesthetics. Analgesic effects of anesthetics may be related to alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor [4,5,6], benzodiazepine receptor [7], N-methyl-D-Aspartate receptor [8,9,10], glycine receptor [11,12,13,14], nerve nicotinic receptors [15], and alpha 2 receptors [16] on the spinal cord. Morphological and molecular biology research has indicated that the 5-serotonin receptor 1A (5-HT 1A R) is widely distributed in the nervous system.…”
mentioning
confidence: 99%